Frequency of Helicobacter pylori infection and antibiotic resistance in patient whit acute liver decompensation - Ristić, Milica; Korica, Bojan; Milivojević, Vladimir (Medicinski podmladak, 2024)
Introduction: Helicobacter pylori (H. pylori) infection is a global healthcare challenge. In its course of infection, Helicobacter pylori infection leads to a systemic increase of post-inflammatory cytokines and can have an extragastric manifestations, affecting the worsening of metabolic and cardiovascular diseases and endangering normal liver function, especially when liver cirrhosis is present. Aim: The aim of this study was to examine the frequency of H. pylori infection in patients with cirrhosis of the liver in stage AD or ACLF. The frequency of antibiotic resistence to clarithromycin and fluoroquinolones was also investigated. Material and methods: We conducted prospective study with 45 patients which included both sexes. Samples of gastric mucosa were taken from all patients included in the study during the upper endoscopy and were sent to the Institute of Microbiology of the Medical Faculty in Belgrade. A molecular method, Polymerase chain reaction (PCR) was used to detect H. pylori and mutations responsible for resistance to clarithromycin and fluoroquinolones. Results: The presence of H. pylori infection was registered in 15 decompensated patients (33,33%), while 30 (66,67%) were negative. In H. pylori positive patients, PCR detection of genotypes responsible for antibiotic resistance revealed clarithromycin resistance in 11 patients (73,33%), while fluoroquinolone resistance was detected in 7 patients (46,66%). In 6 patients (40,0%) was found a associated resistance to clarithromycin and fluoroquinolones. Conclusion: H. pylori infection in cirrhotic patients with acute decompensation or ACLF has no significant effect on the severity of the clinical condition, elevated laboratory parameters and survival. Resistance rates to fluoroquinolones and clarithromycin or both antibiotics are high in decompensated patients with cirrhosis. There is a need to increase awareness of the rational use of antibiotics based on further investigations